A systematic review of factors influencing habitat connectivity and biodiversity along road and rail routes in temperate zones - Cork, Nicholas A.; Fisher, Rachel S.; Strong, Neil; Ferranti, Emma J. S.; Quinn, Andrew D. (Frontiers in Environmental Science, 2024)
This systematic review, part funded by Network Rail Ltd (UK), considers the role of transportation corridors in habitat connectivity within temperate climates, through verge habitat, surrounding matrix, movement along and across the corridor, the wider landscape context and management practices. PICO terms were developed for the bibliographic search on 15/11/22 using Web of Science (all databases), yielding 168 studies for review. The risk of bias was minimised by excluding non-peer reviewed papers. Large and exotic taxa were excluded due to a focus on temperate zones, as were studies on invasive species and climate change where the primary focus was not ecological connectivity. Emergent themes were used to structure the paper. Results indicate that transportation corridors have significant potential for habitat connectivity, especially for generalist and open-specialist species, which favour early to mid-successional habitats. However, physiology is a key determinant in dispersal ability. Vegetation management should consider representative communities rather than individual species. Gaps exist in the range of taxa studied, understanding of seasonal variations and lifecycle stages supported in verges, survival factors such as predation and disease and changes to community structure. Rail environments are under-represented and there is limited knowledge on the relative impacts of vegetation management regimes.